Differentiated postnatal growth of the neurocranium and splanchnocranium in domestic equines - Parés-Casanova, Pere M. (2018)
Geometric morphometry of 42 equine skulls from different domestic breeds was used. A digital photograph of the dorsal plane of each skull was obtained, on which were placed seven craniometric landmarks, involving both the neuro and the splanchnocranium. It is verified that the ontogenic process of domestic equids conforms to the CREA rule (Cranial Evolutionary Allometric), by which there is a common allometric pattern among taxa of mammals, by which the smaller species would have shorter faces and skulls wider than larger species. A dolichoprosopy correlated with dolichocephaly is accepted, or in other words, a facial hypermorphosis (since the facial width also has a behavior similar to that of the length of the face) parallel to the increase in the size of the head for domestic equids.